Autogenous cerebral processes: an invitation to look at the brain from inside out - Maldonado, Pedro E.; Concha-Miranda, Miguel; Schwalm, Miriam (Frontiers in Neural Circuits, 2023)
While external stimulation can reliably trigger neuronal activity, cerebral processes can operate independently from the environment. Here, we conceptualize Autogenous Cerebral Processes (ACP) as intrinsic operations of the brain that exist on multiple scales and can influence or shape stimulus responses, behavior, homeostasis, and the physiological state of an organism. We further propose that the field should consider exploring to what extent perception, arousal, behavior, or movement, as well as other cognitive functions, previously investigated mainly regarding their stimulus-response dynamics, are actually ACP-driven.